CHINGIZ AITMATOV'S NOVEL "THE DAY OF THE CENTURY" (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article talks about the stages of development of the novel genre in the work of Chingiz Aitmatov, a great figure of world literature of the 20th century, the uniqueness of the author's skill in this regard, and his very valuable work "The Day of the Century". Instead, the artistic interpretation of the human spiritual world is briefly described on the example of the characters of the novel.